Penanaman Nilai Religius kepada Mahasiswa melalui Tahsin Al-Qur’an Bermuatan Sains - Lutfiyanti Fitriah; Gita Trisnawati (Borneo Research and Educatin Center, 2021)
The background of this community service activity was the need for continuous instilling of religious values to students so that they could internalize these values properly. The purpose of this community service was to instill religious values into students through Tahsin Al-Qur'an activities where the verses were relevant to science. This activity was carried out online and offline at the Ma'had Al-Jami'ah Dormitory II of UIN Antasari Banjarmasin from February to November 2021. The methods used in this service were assignments, exercises, and lectures. The number of service participants was 41 students of UIN Antasari Banjarmasin. The Tahsin Al-Qur'an was carried out well. After this activity was carried out, students could read the Qur'an properly and correctly and recognized the verses of the Qur'an that contain science.